Lecture notes on electron correlation and magnetism - Fazekas, Patrik (Series in modern condensed matter physics ;, 1999)
"This volume attempts to fill the gap between standard introductions to solid state physics, and textbooks which give a sophisticated treatment of strongly correlated systems. Starting with the basics of the microscopic theory of magnetism, one proceeds with relatively elementary arguments to such topics of current interest as the Mott transition, heavy fermions, and quantum magnetism. The basic approach is that magnetism is one of the manifestations of electron-electron interaction, and its treatment should be part of a general discussion of electron correlation effects. Though the text is primarily theoretical, a large number of illustrative examples are brought from the experimental literature. There are many problems, with detailed solutions. The book is based on the material of lectures given at the Diploma Course of the International Center for Theoretical Physics, Trieste, and later at the Technical University and the R. Eötvös University of Budapest, Hungary."